Concordance of the ForenSeq™ system and characterisation of sequence-specific autosomal STR alleles across two major population groups. (May 2018) - Devesse, Laurence; Ballard, David; Davenport, Lucinda; Riethorst, Immy; Mason-Buck, Gabriella; Syndercombe Court, Denise
Abstract: By using sequencing technology to genotype loci of forensic interest it is possible to simultaneously target autosomal, X and Y STRs as well as identity, ancestry and phenotypic informative SNPs, resulting in a breadth of data obtained from a single run that is considerable when compared to that generated with standard technologies. It is important however that this information aligns with the genotype data currently obtained using commercially available kits for CE-based investigations such that results are compatible with existing databases and hence can be of use to the forensic community. In this work, 400 samples were typed using commercially available STR kits and CE, as well as using the Ilumina ForenSeq™ DNA Signature Prep Kit and MiSeq ® FGx to assess concordance of autosomal STRs and population variability. Results show a concordance rate between the two technologies exceeding 99.98% while numerous novel sequence based alleles are described. In order to make use of the sequence variation observed, sequence specific allele frequencies were generated for White British and British Chinese populations.